Stress-induced anhedonia in mice is associated with deficits in forced swimming and exploration - Strekalova, Tatyana; Spanagel, Rainer; Bartsch, Dusan; Henn, Fritz A.; Gass, Peter (Neuropsychopharmacology, 2004)
In order to develop a model for a depression-like syndrome in mice, we subjected male C57BL/6 mice to a 4-week-long chronic stress procedure, consisting of rat exposure, restraint stress, and tail suspension. This protocol resulted in a strong decrease in sucrose preference, a putative indicator of anhedonia in rodents. Interestingly, predisposition for stress-induced anhedonia was indicated by submissive behavior in a resident-intruder test. In contrast, most mice with nonsubmissive behavior did not develop a decrease in sucrose preference and were regarded as nonanhedonic. These animals were used as an internal control for stress-induced behavioral features not associated with the anhedonic state, since they were exposed to the same stressors as the anhedonic mice. Using a battery of behavioral tests after termination of the stress procedure, we found that anhedonia, but not chronic stress per se, is associated with key analogues of depressive symptoms, such as increased floating during forced swimming and decreased exploration of novelty. On the other hand, increased anxiety, altered locomotor activity, and loss of body weight were consequences of chronic stress, which occurred independently from anhedonia. Thus, behavioral correlates of stress-induced anhedonia and of chronic stress alone can be separated in the present model.